2023
DOI: 10.1186/s13098-023-01178-8
|View full text |Cite
|
Sign up to set email alerts
|

System inflammation response index: a novel inflammatory indicator to predict all-cause and cardiovascular disease mortality in the obese population

Fanliang Kong,
Junhao Huang,
Chunhua Xu
et al.

Abstract: Aim This study aims to investigate the relationship between two novel inflammatory markers, namely, the Systemic Inflammatory Response Index (SIRI) and the Systemic Immune Inflammatory Index (SII), as well as the all-cause and cardiovascular disease (CVD) mortality in the obese population. Materials and methods We conducted a prospective cohort study based on the data of 13,026 obese adults (age ≥ 18 years) from the National Health and Nutrition Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…Also, SIRI was found to be an independent predictor of in-hospital death in older patients with acute myocardial infarction (odds ratio [OR] = 3.948, 95% CI: 1.910–8.158) ( 23 ). In addition, this positive association between SIRI and mortality has been observed in other diseases (e.g., cancer, coronary artery disease, stroke, asthma, obesity) ( 20 22 , 25 28 ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Also, SIRI was found to be an independent predictor of in-hospital death in older patients with acute myocardial infarction (odds ratio [OR] = 3.948, 95% CI: 1.910–8.158) ( 23 ). In addition, this positive association between SIRI and mortality has been observed in other diseases (e.g., cancer, coronary artery disease, stroke, asthma, obesity) ( 20 22 , 25 28 ).…”
Section: Discussionmentioning
confidence: 68%
“…More recently, the system inflammation response index (SIRI) has been considered as a novel marker that comprehensively reflects the balance between host inflammatory and immune status ( 20 ). Emerging studies indicated that high SIRI level was closely associated with poor prognosis in many diseases, including cancer (e.g., liver cancer, prostate cancer) ( 20 , 21 ), cardiovascular disease (e.g., coronary artery disease, myocardial infarction) ( 22 24 ), cerebrovascular disease (e.g., stroke, intracerebral hemorrhage) ( 25 , 26 ), respiratory disease (e.g., asthma) ( 27 ), and obesity ( 28 ). The SIRI is calculated from peripheral neutrophil, monocyte and lymphocyte ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the SIRI demonstrated better prognostic discrimination for adverse clinical outcomes than did the CRP [ 33 ]. An elevated SII/SIRI has also been associated with increased risks of all-cause or cardiovascular mortality in individuals with obesity [ 34 ], nonalcoholic fatty liver disease [ 35 ], diabetes [ 36 ], and ischemic stroke [ 17 ]. Research on the utility of the SII and SIRI in OA has been limited, with very few studies examining their potential roles as biomarkers in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this study also collected laboratory data upon patient admission, including white blood cell count (WBC), red blood cell count (RBC), hemoglobin (HGB), mean corpuscular hemoglobin concentration (MCHC), mean corpuscular volume (MCV), neutrophils (NC), lymphocytes (LYM), monocytes (MONO), eosinophils (Eos), basophils (Baso), albumin (ALB), aspartate aminotransferase (AST), alanine aminotransferase (ALT), total bilirubin (TBIL), creatinine (Cr), blood urea nitrogen (BUN), prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen (FIB), and other relevant data. The inflammatory factor validated in this study is calculated as the systemic inflammatory response index (SIRI) using the formula: SIRI = (neutrophil count × monocyte count)/lymphocyte count [ 19 ].…”
Section: Methodsmentioning
confidence: 99%